A multicenter evaluation of external outflow graft obstruction with a fully magnetically levitated left ventricular assist device - Wert, Leonhard; Stewart, Garrick C; Mehra, Mandeep R; Milwidsky, Assi; Jorde, Ulrich P; Goldstein, Daniel J; Selzman, Craig H; Stehlik, Josef; Alshamdin, Faisal D; Khaliel, Feras H; Gustafsson, Finn; Boschi, Silvia; et al. (Journal of thoracic and cardiovascular surgery, 2024)
BACKGROUND: The HeartMate 3 (HM 3; Abbott) left ventricular assist device (LVAD) has improved hemocompatibility-related adverse outcomes. In sporadic cases, external compression of the outflow graft causing obstruction (eOGO) can result from substance accumulation between the outflow graft and its bend relief. We sought to evaluate the prevalence, course, and clinical implications of eOGO in an international study. METHODS: A multicenter retrospective analysis of HM 3 LVADs implanted between November 2014 and April 2021 (n = 2108) was conducted across 17 cardiac centers in 8 countries. We defined eOGO as obstruction >25% in the cross-sectional area in imaging (percutaneous angiography, computed tomography, or intravascular ultrasound). The prevalence and annual incidence were calculated. Serious adverse events and outcomes (death, transplantation, or device exchange) were analyzed for eOGO cases. RESULTS: Of 2108 patients, 62 were diagnosed with eOGO at a median LVAD support duration of 953 (interquartile range, 600-1267) days. The prevalence of eOGO was 3.0% and the incidence at 1, 2, 3, 4, and 5 years of support was 0.6%, 2.8%, 4.0%, 5.2%, and 9.1%, respectively. Of 62 patients, 9 were observed, 27 underwent surgical revision, 15 underwent percutaneous stent implantation, 8 received a heart transplant, and 2 died before intervention. One patient underwent surgical revision and later stent implantation. The mortality with therapeutic intervention was 9/53 (17.0%). CONCLUSIONS: Although uncommon, HM 3 LVAD-supported patients might develop eOGO with an increasing incidence after 1 year of support. Although engineering efforts to reduce this complication are under way, clinicians must maintain a focus on early detection and remain vigilant.
Keywords: Heart Failure; Heart Transplantation; Heart-Assist Devices; Humans; retrospektivní studie; lidé; srdeční selhání; podpůrné srdeční systémy; Retrospective Studies; Tomography, X-Ray Computed; transplantace srdce; počítačová rentgenová tomografie